Interactive character posing with efficient collision handling. (4th March 2020) - Kim, Jongmin; Seol, Yeongho; Kim, Hoemin; Kwon, Taesoo
Abstract: An interactive interface for character posing is important in the field of computer graphics, games, and virtual reality. The inverse kinematics (IK) solver is the most popular approach that satisfies both the kinematic equations and the user‐defined position and orientation constraints on the end‐effectors. In this article, we present a novel interactive IK framework that efficiently handles various types of collisions and the spatial relationship constraints during the character posing process. Based on our method, a desired human pose can be easily obtained while resolving a collision with the environment and maintaining the spatial relationship of body parts. In addition, the character pose is smoothly updated throughout the user manipulation. Abstract : Our novel interactive IK framework efficiently handles various types of collisions and the spatial relationship constraints during the character posing process.